Development of Performance Evaluation Model for Elementary Schools Implementing Inclusive Education - Nur'aini, Siti; Purnawanto, Ahmad Teguh (JURNAL PEDAGOGY, 2025)
The purpose of this research is to develop an Inclusive Education Performance Evaluation (IEPE) Model in Elementary Schools (ES). This research uses a Mixed Methods approach. The research method was modified from the Borg & Gall model and involves School Principals, Teachers, and Parents. Data were collected through Focus Group Discussion (FGD), interviews, observations, and documentation studies. The research findings show that (1) the IEPE model is one of the best evaluation models based on the assessment results of experts and practitioners of inclusive education implementation in elementary schools; (2) the performance evaluation model for elementary schools implementing inclusive education consists of seven components: leadership, strategic planning, focus on students-parents, needs analysis, focus on teachers-staff, inclusive classroom management, and results; and (3) the evaluation of the IEPE model in the implementation process at elementary schools is capable of revealing data that is: (a) comprehensive; (b) factual; (c) flexible; and (d) diversity-oriented service.